2008
DOI: 10.1111/j.1365-2648.2007.04544.x
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement and aggression in the operating theatre

Abstract: Further research is needed to conceptualize the complex nature of interprofessional working in operating theatres before steps can be taken to develop a less stressful and more efficient working environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 44 publications
4
54
4
3
Order By: Relevance
“…First, given the simulation-based study design, external validity may be questioned. Nevertheless, hospital-based research on incivility and its consequences 19,[40][41][42][43] suggests that our findings are consistent with the "real world" and, if anything, underestimate the magnitude of effects. Moreover, simulations are becoming more widespread in medicine as an investigative tool.…”
Section: Figuresupporting
confidence: 70%
“…First, given the simulation-based study design, external validity may be questioned. Nevertheless, hospital-based research on incivility and its consequences 19,[40][41][42][43] suggests that our findings are consistent with the "real world" and, if anything, underestimate the magnitude of effects. Moreover, simulations are becoming more widespread in medicine as an investigative tool.…”
Section: Figuresupporting
confidence: 70%
“…A study by Coe and colleagues (2008) showed that 69% of the respondents reported a disagreement between surgeons and theatre nurses, which is similar with our finding (72%). In addition, 77% of our respondents reported an experience of an aggressive behaviour by consultant surgeons and 62% by consultant anaesthesiologists within the last six months, which is much higher compared to the percentage reported in the UK-based study (62% and 34.5% respectively) (Coe 2008). The finding, that junior doctors were showing an aggressive behaviour in lower rates (11%), corroborate earlier studies in the UK and other countries (Coe 2008, Rowe 2005.…”
Section: Main Findingscontrasting
confidence: 40%
“…A detailed description of the questionnaire's structure is presented elsewhere (Coe 2008). In summary, the questionnaire was divided into seven main sections and consisted of 31 questions.…”
Section: Questionnairementioning
confidence: 99%
“…This finding contrasts with studies that suggest that conflicts in the operating theatre are more common between doctors and theatre nurses (Booij 2007;Coe and Gould 2007). Nevertheless disagreements over roles, schedules and goals, which were noted as the causes of the conflicts between doctors and theatre nurses (Coe and Gould 2007), were also some of the causes of the conflicts between doctors and nurse-anaesthetists in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…Similarly Katz's (2007) study notes that poor conflict management destroys professional relationships and team work, which is essential for client care. Other studies suggest that conflicts are common in health care organisations in most parts of the world including the UK (Coe and Gould 2007) and the USA (Rosenstein 2011).…”
Section: Discussionmentioning
confidence: 99%